Clinicopathologic study of mantle cell lymphoma with epstein-barr virus infection: A case series and literature review - Li, Xiaoju; Zhou, Fanlin; Li, Shijie; Wang, Yangyang; Fan, Jianing; Liang, Xiao; Peng, Yan; Jin, Yudi; Jiang, Weiyang; Liu, Fang; Zhou, Yixing; Liu, Shuke; et al. (Frontiers in Oncology, 2022)
Background: Mantle cell lymphoma (MCL) with Epstein–Barr virus (EBV) infection is rarely reported. The objective of this study was to analyze the prevalence and clinicopathological features of MCL with EBV infection in the largest series thus far. Methods: After screening 138 cases of MCL, we identified eight cases of MCL with EBV infection. Results: Most of them (7/8) had non-neoplastic bystander cells with positivity for EBV and no expression of latent membrane protein 1 (LMP1) and EBV nuclear antigen 2 (EBNA2). The cases of MCL with EBER positivity did not have abnormal immune function or other lymphomas. Moreover, their histopathological morphology was indicative of classical MCL. Cases of MCL with EBER positivity exhibited statistically significant differences in lactate dehydrogenase, anemia status, and MCL international prognostic index grouping (P=0.008, P=0.02, P=0.001, and P=0.011, respectively). The differences between the two groups in age, sex ratio, clinical manifestations, and immunohistochemical phenotypes were not statistically significant. Conclusions: The incidence of MCL with EBV infection was low (5.8%). Clinicopathologically, cases of MCL with EBER positivity were similar to their EBV-negative counterparts. Our findings revealed that most cells infected by EBV in MCL are background cells rather than tumor cells. This is inconsistent with data from previous studies, indicating that tumor cells in MCL may not be prone to EBV infection.